Intellectual Property and Technology Management in Dairy Sciences - Singh, Vikram (Indian Journal of Dairy Science, 2015)
Intellectual Property (IP) in dairy sciences at the Indian Council of Agricultural Research (ICAR) such as processes of animal nutrition and dairy food, milk adulteration detection kits, food processing machinery, and other know-how were managed by protecting them as patents at IPO, and transferred to their end-users. A total of 75 patent applications was filed in nine subject specific areas of dairy sciences, out of that 12% were granted for a period of 20 years. As per IPC these applications were fallen under its six classes viz. A, B, C, F, G and H and spread in 22 sub-classes. These IP assets were transferred to 26 public and private organization by signing agreements for 45 partnerships. These transferred technologies belong to six different subject specific areas of dairy science, where transfer of IP protected assets were on its higher side with 34%, which is a success indicator for a research organization. To speed up this process ICAR has taken the initiative with NAIP and established BPD Unit at NDRI, Karnal, which is a leading dairy science institute and also having a functional unit of TBI with the support of DST. With these new business dimensions 20 EDPs were organized, where 300 researchers, entrepreneurs, business organizations and dairy farmers were interacted to use the untapped IPs for the development dairy sector as a profitable business.